Utility of emergent examination using MRI for diagnosis of acute cerebral stroke - Nishitani, Hiroshi; Kaji, Ryuji; Morita, Naomi; Harada, Masafumi; Uno, Masaaki; Nagahiro, Shinji; Izumi, Tadanobu (Japanese Journal of Stroke, 2006)
CT is a widely used imaging modality for diagnosis of cerebral vascular disease. However, the sensitivity of detection at early stage of cerebral infarction is not adequate depending on the ability of observers and instruments. The high sensitivity of diffusion-weighted imaging on MRI for the diagnosis of acute cerebral infarction has bee reported. Furthermore, MRI can demonstrate perfusion and vascular information without usage of contrast medium. In addition, the recent work showed that susceptibility imaging on MRI has the same quality to detect acute cerebral hemorrahge as CT. We consider that MRI has a possibility to become the first selected modality for the acute cerebral infarction.